Entrepreneurial passion, entrepreneurial expectation and entrepreneurial decision-making among college students. Issue 4 (3rd August 2020) - Yi, Rui; Lyu, Bei; Wang, Haojun; Huang, Wenxiang
Abstract : We examined entrepreneurial passion influences on entrepreneurial decision-making, and entrepreneurial expectation among 427 Chinese college students (female = 49.41%; mean age = 20.85 years, SD = 1.13 years). The students completed surveys on entrepreneurial passion, entrepreneurial expectation, entrepreneurial ability, and entrepreneurial decision-making. Results from path analysis indicated students with high entrepreneurial passion scores to also have high entrepreneurial decision-making scores. Students' entrepreneurial expectation mediated the relationship between entrepreneurial passion and college students' entrepreneurial decision-making. The students' entrepreneurial ability moderated the relationship between entrepreneurial passion and entrepreneurial decision-making through entrepreneurial expectation. Entrepreneurial decision-making capabilities of students may provide insights into policies for entrepreneurial practice and education programs.